2005
DOI: 10.1093/carcin/bgi218
|View full text |Cite
|
Sign up to set email alerts
|

Tetraploidy and chromosomal instability are early events during cervical carcinogenesis

Abstract: Chromosomal instability as manifested by increases in aneuploidy and structural chromosome aberrations is believed to play a critical role in the intermediate to late stages in the development of cervical malignancies. The current study was designed to determine the role of tetraploidy in the formation of aneuploidy and ascertain the occurrence of these alterations during the earlier stages of cervical carcinogenesis. Cervical cell samples, with diagnoses ranging from Normal to high-grade lesions, (HSIL) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(175 citation statements)
references
References 61 publications
8
162
0
5
Order By: Relevance
“…Numerous studies have shown that the loss of mitotic regulation contributes to carcinogenesis. [26][27][28] Any inaccuracies during the process of chromosomal segregation results in either a loss or gain of chromosomes, potentially leading to upregulation of oncogenes or down regulation of tumor supressors. 29 Recent in vivo data from Ramadan et al 20 suggests AURKB to be responsible for the prevention of chromatin decondensation during late mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the loss of mitotic regulation contributes to carcinogenesis. [26][27][28] Any inaccuracies during the process of chromosomal segregation results in either a loss or gain of chromosomes, potentially leading to upregulation of oncogenes or down regulation of tumor supressors. 29 Recent in vivo data from Ramadan et al 20 suggests AURKB to be responsible for the prevention of chromatin decondensation during late mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that the suppression of survivin results in cells with multipolar mitotic spindles that are either multinucleated or aneuploid (Li et al, 1999;Beltrami et al, 2004;Kappler et al, 2004). Some studies have also indicated that aneuploidy promotes chromosome instability (CIN) in glioma and cervical carcinoma cells (Nitta et al, 2002;Olaharski et al, 2006).…”
mentioning
confidence: 99%
“…The in vivo mouse bone marrow micronucleus (MN) assay is currently recommended by the International Conference on Harmonization (ICH, 1997), the Food and Drug Administration, and other regulatory agencies (Cimino, 2006) to investigate the genotoxic/ chemopreventive potential of new agents. In addition, a direct connection between increase in MN frequency and development of carcinogenesis has been documented in the literature (Olaharski et al, 2006).…”
Section: Introductionmentioning
confidence: 94%